Case to Cause: Back to the Future. (13th July 2016) - Abramovitz, Mimi; Sherraden, Margaret S.
ABSTRACT: This article reopens the historic debate about the roles of micro and macro practice in social work and encourages the profession to find ways to achieve a better balance between case and cause in education, practice, and research. To this end, it traces the history of the case versus cause debate including conceptual frameworks for rebalancing social work education: Bertha Capen Reynolds, C. Wright Mills, and William Schwartz, highlights three alternative approaches for resolving the dualism put forward over the years; separation, merger and interconnection; and identifies four model that help to bridge the gap by taking both the individual and the social structures into account: ecological, financial capabilities, trauma theory and oppression. This historical analysis offers promising directions for the social work profession as it tackles 21st–century social challenges, including growing inequality and austerity–driven public policies.